Implementation of Inquiry-Based Learning Models to Improve Elementary School Students Exploration Skills - Sutantina, Tri; Matsuri, Matsuri; Supianto, Supianto (Universitas Sebelas Maret, 2026)
This study was motivated by the fact that students' exploration skills in science learning are still relatively low because learning tends to be teacher-centered. This study aims to improve students' exploration skills through the application of the inquiry learning model in science learning. This study is a classroom action research (CAR) conducted in two cycles, with stages of planning, implementation of actions, observation, and reflection. The research subjects were fifth-grade students at SDN 03 Gedong. Data collection techniques were carried out through observation, tests, and documentation. The data were analyzed using quantitative and qualitative descriptive techniques. The results showed that students' exploration skills increased from 62% in cycle I to 86% in cycle II. In addition, the students' IPAS learning outcomes also increased from 65% in cycle I to 88% in cycle II. Based on these results, it can be concluded that the application of the inquiry learning model can improve the exploration skills and IPAS learning outcomes of elementary school students.